From traditional operational research to multiple criteria decision analysis: basic ideas on an evolving field - Ferreira, F.; Santos, S.; Rodrigues, P. (Problems and Perspectives in Management, 2011)
This paper presents the mostrecent evolutionary lines in operational research, through a review of the basic principles that guide this field of research. In broad terms, some emphasis is given to the fact that Multiple Criteria Decision Analysis (or Aid) (MCDA) takes into account that decision-making processes are complex and composed of several actors with different perceptions and value systems, stressing that this approach highlights the limits of objectivity, and considers the possibility that some problems may not have an optimal solution. In this vein, it is beyond the scope of this paper to discuss the modeling of particular problems or to present empirical results. Instead, our study aims to consider, share points of view and/or promote a deeper discussion among researchers who use MCDA. By highlighting some of the main characteristics of MCDA and contributing to the MCDA diffusion, this paper might be a starting point to forecast potential developments in the field.